A Minimal Model Illuminates the Physics of Pulse‐Like Seismic Rupture and Oscillatory Slip Rates in Damaged Faults - Fabian Barras; Einat Aharonov; François Renard (Geophysical Research Letters, 2025)
Abstract Fault zones are often surrounded by a damage zone that exhibits lower seismic velocities than the wall rock, influencing earthquake propagation and arrest. We present a one‐dimensional minimal model of frictional rupture that approximates the elastodynamics of a fault embedded within a damage zone. This model predicts two families of steady‐state rupture solutions: an overdamped regime, describing a crack‐like rupture, and an underdamped regime with oscillating slip‐rate in the wake of the rupture, which promotes pulse‐like dynamics. The minimal model contains two free parameters: the pre‐stress on the fault, and the seismic velocity reduction in the damage zone. We present how the one‐dimensional prediction is consistent with previously published two‐dimensional simulations and discuss the applicability of our results to natural observations, identifying the preferred rupture style as function of structure of the fault zone, and the geological consequences of oscillatory slip in the wake of pulse‐like ruptures.